Synthesis and Molecular Docking Studies of New Series of Bis-Schiff Bases Thiadiazoles Derived From Disulfides and Thioethers with Potent Antibacterial Properties - Hamad, Hardi Q.; Taher, Salam G.; Aziz, Dara M. (Science Journal of University of Zakho, 2022)
Two new series of various heterocyclic bis-Schiff bases of Thiadiazoles disulfides and thioethers are synthesized. The first series was the synthesis of bis-Schiff of thiadiazole disulfides (4a-h) synthesized from their corresponding Schiff bases after oxidation by hydrogen peroxide. The second series was the synthesis of bis-Schiff base thiadiazole thioethers (7a-h). It was obtained from the reaction of bis-thiadiazole diamine (6) with different aldehyde. The diamine (6) was generated by reacting thiadiazole with dibromoethane in dimethylformamide and triethylamine as a catalyst. All of the synthesized compounds were analyzed by using FT-IR, 1H-NMR, 13C-NMR, and C-APT techniques. The synthesized compounds were screened against two gram-positive bacteria (Staphylococcus and streptococcus), and two strains of gram-negative (E. coli and klebsiella) in comparison to two standard strong antibiotic drugs (ciprofloxacin and vancomycin). Generally, all the synthesized compounds showed highly antibacterial properties, particularly, compounds (4b,4f, and 7b) which observed potent anti-bacterial properties against both gram- (positive, negative) bacteria were even higher than the standard drugs. Lastly, molecular docking studies were also applied to find the binding affinity and active sides of the products with the target proteins.